Arang Aktif Batok Kelapa (Cocos nucifera) sebagai Adsorben - Novia Nurul Aini; Ratna Djuniwati Lisminingsih; Saimul Laili (FMIPA UNISMA, 2021)
The fish processing industry is one of the important elements in improving the standard of living of the Indonesian people, but the industry also produces waste in the form of crude fish oil which is bad for the environment if it is not processed first before being discharged into the environment. Reducing the problem of fish processing industry waste requires processing fish oil into useful goods, for example reprocessing it into pure oil which is useful in non-food industries such as being used as a mixture of fish feed. The purification of crude fish oil is carried out in three stages, namely the degumming, neutralization, and bleaching stages using coconut shell activated charcoal adsorbent. The purpose of this study was to determine whether giving coconut shell activated charcoal with different weight has the potential in the bleaching process of crude fish oil from fish processing industrial waste. This research uses experimental methods. The bleaching stage used different weight of coconut shell activated charcoal, namely 0% (control), 2%, 4%, 6%, and 8%. The parameters measured were free fatty acid levels and clarity values. Free fatty acid content in all treatments <1% and in accordance with the Indonesian national standard (SNI). ANOVA test results on the mean free fatty acids showed no significant difference between treatments. Similarly, the ANOVA test on clarity values showed no significant difference. Provision of coconut shell activated charcoal has the potential as an adsorbent in the bleaching process of crude fish oil, fish processing industry waste.Keywords: Crude Fish Oil, Bleaching, Coconut Shell Activated Charcoal. ABSTRAKIndustri pengolahan ikan merupakan salah satu unsur penting dalam meningkatkan taraf hidup bangsa Indonesia, tetapi industri tersebut juga menghasilkan limbah berupa minyak ikan kasar yang berdampak buruk bagi lingkungan apabila tidak diolah terlebih dahulu sebelum dibuang ke lingkungan. Mengurangi permasalahan limbah industri pengolahan ikan, membutuhkan pengolahan minyak ikan menjadi barang yang berguna misalnya mengolah kembali menjadi minyak murni yang berguna dalam indutri non pangan seperti digunakan sebagai bahan campuran pakan ikan. Pemurnian minyak ikan kasar ini dilakukan tiga tahapan yakni tahap degumming, netralisasi, dan bleaching menggunakan adsorben arang aktif batok kelapa. Tujuan dari penelitian ini adalah untuk mengetahui apakah pemberian arang aktif batok kelapa dengan berat berbeda berpotensi dalam proses pemutihan (Bleaching) minyak ikan kasar dari limbah industri pegolahan ikan. Penelitian ini menggunakan metode eksperimental. Tahapan bleaching menggunakan berat arang aktif batok kelapa yang berbeda yakni 0% (kontrol), 2%, 4%, 6%, dan 8%. Parameter yang diukur adalah kadar asam lemak bebas dan nilai kejernihan. Kadar asam lemak bebas pada semua perlakuan < 1% dan telah sesuai dengan standar nasional Indonesia (SNI). Hasil uji ANOVA terhadap rerata asam lemak bebas menunjukkan tidak ada perbedaan yang signifikan antar perlakuan. Sama halnya dengan uji ANOVA terhadap nilai kejernihan menunjukkan tidak ada perbedaan yang signifikan. Pemberian arang aktif batok kelapa berpotensi sebagai adsorben pada proses bleaching minyak ikan kasar limbah industri pengolahan ikan.Kata kunci: Minyak Ikan Kasar, Bleaching, Arang Aktif Batok Kelapa